APOCALYPSE LAKARDOWO: ECOCRITICAL ANALYSIS IN THE FILM LAKARDOWO MENCARI KEADILAN - Maulida, Aulia; Basid, Abdul (UI Scholars Hub, 2019)
Human-nature interaction today enters a worrying stage. Film as a literary work begins to record this interaction. The film Lakardowo Mencari Keadilan to be one of them. This research uses the content analysis method with an ecocritical approach. This film is a research primary data source supported by various related references. The analysis emphasizes the study of environmental literature which focuses on apocalyptic reading with pastoral views that surround it through Creswell spiral analysis methods: data management, reading, and note-taking, classification and interpretation, then data visualization. In this research, Lakardowo's environment in the film Lakardowo Mencari Keadilan reflects the impact of B3 waste pollution that's not carried out by the community. Pollution of B3 waste on land, water, and air in Lakardowo clearly record through analysis of the apocalyptic narrative as a disaster for Lakardowo village. Whereas the hopes of the community of responses to B3 waste in Lakardowo is conveying in aspects of the reading of pastoral narratives.